The competing jurisdictions of international courts and tribunals - Shany, Yuval (O.U.P. OxfordGB, 2003)
Explores the implications of jurisdictional competition. Identifies standards that may alleviate problems associated with the phenomenon, which arguably threatens the unity of international law.